Building ‘Tough Student Character’ through Optimization of Spiritual and Emotional Intelligence: An Action Research - Fadlil Yani Ainusyamsi *, Husni Husni (International Journal of Advanced Science and Technology, 2020)
This article aims to build a tough student character through the optimization of spiritual intelligence and social intelligence. This participatory action research was conducted at the Madrasah Tsanawiyah Negeri Cijeungjing, Ciamis-Indonesia, a religious education institution located in suburban areas. The results showed that the optimization of emotional intelligence works effectively in building tough student character, with a correlation coefficient of 0.72. This study also proves that the optimization of spiritual intelligence works effectively in building tough student character with a correlation coefficient of 0.69. The combination of emotional intelligence and spiritual intelligence has a significant effect on building tough student character, which is indicated by the number of multiple correlation coefficients of 0.73. Thus, optimizing spiritual intelligence and spiritual intelligence simultaneously contributes approximately 53% to the character of students.